Sustainable Corporate Governance – The Purpose of the Company - Boeva, Bistra (UNWE Yearbook, 2021)
The objective of this paper is to explore the latest trends in sustainable corporate governance with а focus on the purpose of the company. Referring to her previous research projects and publications, the author aims to build on the preceding findings and research results. The objective of the paper is to give an answer to whether company purpose (the new mantra) is a totally new concept within the framework of corporate governance or, in other words, whether the business community has changed completely and whether a new business model has been developed by academia, consultants and business leaders. To answer these questions the author has initiated a literature survey and web mining to get a fresh perspective from the corporate practices in the EU and US economies. Experts’ views and judgement are discussed in order to obtain information about the agenda and priorities of listed Bulgarian companies.The paper is structured as follows: overview of sustainable corporate governance (introduction); survey on the academic views on the purpose of the company (part one); investigation of the business views on the purpose (part two) and the corporate governance agenda – shareholders’ perspective on the purpose studies (part four) and conclusions and suggestions for future research.